Parasitic foraminifers on a deep-sea chiton (Mollusca, Polyplacophora, Leptochitonidae) from Iceland - Sigwart, Julia (Marine Biology Research, 2009)
Epibiotic foraminifers selectively settle on the most food-rich area of the host substrate, even when the species acts as a facultative ectoparasite in later life stages. In 398 specimens examined of the deep-sea chiton Leptochiton arcticus from Iceland, 46% show evidence of infestation by foraminifers, with many showing extensive shell damage from present and past bioeroding epibionts. Disturbances to the inner layer of the host shell are indicative of parasitism, as evidenced both by wound healing calcification and protrusions of the foraminiferan tubules. The epibionts employ different feeding strategies at different stages of their life cycle, taking advantage of nutrient availability from the posterior respiration currents and excrement of the chitons as juveniles, and feeding parasitically as adults. Epibiont persistence on individual hosts-through successive generations, or long-term continuous bioerosion by epibionts-allow larger adult parasitic foraminifers of Hyrrokkin sarcophaga to penetrate the thick tail valve of a chiton and feed parasitically on the host tissue. The proportion of chitons infested increases with host size, indicating that epibionts are accumulated through a chiton's life, seemingly without major detriment to host survivorship.